A Case of Disseminated Cutaneous Herpes Simplex Virus-1 as the First Manifestation of Human Immunodeficiency Virus Infection - Parker Brown BS; Sandra Elmasry BS; Abdulbaril Olagunju MD; Santiago Garcia MD; Mansi Sarihan MD (SAGE Publishing, 2021)
Reported clinical manifestations of active herpes simplex virus type 1 (HSV-1) infection include typically painful vesicular cutaneous rash in a dermatomal distribution, temporal lobe encephalitis, and rarely, fulminant septic shock with multiorgan failure. In immunocompromised patients, the cutaneous rash can become disseminated. We report a case of a 33-year-old male patient with undiagnosed human immunodeficiency virus (HIV) infection who presented to our emergency department (ED) with a disseminated cutaneous rash. The rash was extensive, involved 90% of his total body surface area. It began 5 days prior as small ulcerations localized to the left arm, sought care at an outside ED, diagnosed as severe dermatitis with bacterial superinfection and discharged with a cephalexin prescription. Laboratory results were positive for HIV test with a CD4 count of 254, white blood cell count (WBC) of 7.4 k/microL with 54% neutrophils, 9% lymphocytes, 0% eosinophils, 0% basophils, and serum creatinine and sodium of 3.05 mg/dL and 119 mEq/L, respectively. The burn team and dermatology ruled out Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis due to the absence of mucosal involvement, negative nikolsky sign, and absence of skin sloughing. Polymerase chain reaction of samples obtained from the skin lesions was positive for HSV-1. The rash resolved with intravenous acyclovir and was started on highly active antiretroviral therapy (HAART) on outpatient follow-up. To the best of our knowledge, comparable cases of significantly disseminated cutaneous HSV-1 infection as the initial presentation of HIV infection have been rarely reported.